Method to measure the mismatch between target and achieved received dose intensity of chemotherapy in cancer trials: a retrospective analysis of the MRC BO06 trial in osteosarcoma. Issue 5 (30th May 2019) - Lancia, Carlo; Anninga, Jakob; Spitoni, Cristian; Sydes, Matthew R.; Whelan, Jeremy; Hogendoorn, Pancras C W; Gelderblom, Hans; Fiocco, Marta
Abstract : Objectives: In cancer studies, the target received dose intensity (tRDI) for any regimen, the intended dose and time for the regimen, is commonly taken as a proxy for achieved RDI (aRDI), the actual individual dose and time for the regimen. Evaluating tRDI/aRDI mismatches is crucial to assess study results whenever patients are stratified on allocated regimen. The manuscript develops a novel methodology to highlight and evaluate tRDI/aRDI mismatches. Design: Retrospective analysis of a randomised controlled trial, MRC BO06 (EORTC 80931). Setting: Population-based study but proposed methodology can be applied to other trial designs. Participants: A total of 497 patients with resectable high-grade osteosarcoma, of which 19 were excluded because chemotherapy was not started or the estimated dose was abnormally high (>1.25 × prescribed dose). Intervention(s): Two regimens with the same anticipated cumulative dose (doxorubicin 6×75 mg/m 2 /week; cisplatin 6×100 mg/m 2 /week) over different time schedules: every 3 weeks in regimen-C and every 2 weeks in regimen-DI. Primary and secondary outcome measures: tRDI distribution was measured across groups of patients derived from k-means clustering of treatment data. K-means creates groups of patients who are aRDI-homogeneous. The main outcome is the proportion of tRDI values in groups of homogeneous aRDI. Results: For nearly half of the patients, there is a mismatch between tRDI and aRDI; for 21%, aRDI was closer to the tRDI of the other regimen. Conclusions: For MRC BO06, tRDI did not predict well aRDI. The manuscript offers an original procedure to highlight the presence of and quantify tRDI/aRDI mismatches. Caution is required to interpret the effect of chemotherapy-regimen intensification on survival outcome at an individual level where such a mismatch is present. The study relevance lies in the use of individual realisation of the intended treatment, which depends on individual delays and/or dose reductions reported throughout the treatment. Trial registration number: ISRCTN86294690 .